The Long‐Run Negative Drift of Post‐Listing Stock Returns - DHARAN, BALA G.; IKENBERRY, DAVID L. (Journal of Finance, 1995)
ABSTRACT After firms move trading in their stock to the American or New York Stock Exchanges, stock returns are generally poor. Although many listing firms issue equity around the time of listing, post‐listing performance is not entirely explained by the equity issuance puzzle. Similar to the conclusions regarding other long‐run phenomena, poor post‐listing performance appears related to managers timing their application for listing. Managers of smaller firms, where initial listing requirements may be more binding, tend to apply for listing before a decline in performance. Poor post‐listing performance is not observed in larger firms.